2013
DOI: 10.1021/jf3042402
|View full text |Cite
|
Sign up to set email alerts
|

Momordica charantia and Its Novel Polypeptide Regulate Glucose Homeostasis in Mice via Binding to Insulin Receptor

Abstract: Momordica charantia (MC) has been used as an alternative therapy for diabetes mellitus. This study analyzed and elucidated therapeutic targets contributing to the hypoglycemic effect of aqueous extract of MC seeds (MCSE) by transcriptomic analysis. Protein ingredients aimed at the hypoglycemic target were further identified by proteomic, docking, and receptor-binding assays. The data showed that MSCE (1 g/kg) significantly lowered the blood glucose level in normal and diabetic mice. Moreover, MCSE primarily re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 42 publications
1
63
0
2
Order By: Relevance
“…This peptide presents 68 amino acid residues and the insulin receptor binding protein of M. charantia (mcIRBP). It acts by activating insulin receptor signaling pathways and stimulating both the uptake and release of glucose in rat cells [56, 57]. Confirming these data, mcIRBP-19 was observed to be the peptide insulin receptor binding motif of mcIRBP with a similar ability for glucose uptake [58].…”
Section: Discussionmentioning
confidence: 87%
“…This peptide presents 68 amino acid residues and the insulin receptor binding protein of M. charantia (mcIRBP). It acts by activating insulin receptor signaling pathways and stimulating both the uptake and release of glucose in rat cells [56, 57]. Confirming these data, mcIRBP-19 was observed to be the peptide insulin receptor binding motif of mcIRBP with a similar ability for glucose uptake [58].…”
Section: Discussionmentioning
confidence: 87%
“…GSK-3 is one of the negative regulators in the hormonal control of glucose homeostasis which are involved in the carbohydrate metabolism through the mechanism of phosphorylation and inactivation of the enzyme glycogen synthase. The novel IR-binding protein (Trypsin inhibitor) was isolated from aqueous extract of M. charantia seeds, which lowered blood sugar levels by regulating the insulin signaling pathway in muscles and adipose tissues and stimulating the IRdownstream pathway [49]. M. charantia extract also considered as an herbal remedy for type-II diabetes, contains a specific 11β-hydroxysteroid dehydrogenase type 1 inhibitor, responsible for reducing the PPARA gene expression [46].…”
Section: Anti-diabetic Activitymentioning
confidence: 99%
“…Previously similar studies using protein extracts from the fruits of Momordica charantia showed insulin secretagogue and insulinomimetic activities in STZ induced diabetic rats [38]. Identification of insulin receptor binding-peptide from Momordica charantia [39] signifies the presence of phytohormones that are capable of regulating insulin signaling pathways.…”
Section: Discussionmentioning
confidence: 94%